2020
DOI: 10.1111/itor.12767
|View full text |Cite
|
Sign up to set email alerts
|

An effective algorithm for flexible assembly job‐shop scheduling with tight job constraints

Abstract: Thus far, the available works on the flexible assembly job‐shop scheduling problem (FAJSP) consider job processing and assembly separately. However, in some real production systems, if equipment is composed of thousands of jobs and assembled in many stages, some jobs and assemblies cannot be processed simultaneously. Therefore, this work proposes an FAJSP with tight job constraints (FAJSP‐JC) in which jobs and assemblies can be processed simultaneously, and each assembly is treated as an operation. A job const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Particle swarm optimization algorithm is proposed by [11] to solve a medium size instance. A job constraint genetic algorithm is presented by [35] for FAJSS to minimize the makespan. [36] takes makespan, total tardiness and total workload as optimizing objectives, a distributed ant colony system is proposed to explore the pareto front of FAJSS.…”
Section: Sets and Indicesmentioning
confidence: 99%
“…Particle swarm optimization algorithm is proposed by [11] to solve a medium size instance. A job constraint genetic algorithm is presented by [35] for FAJSS to minimize the makespan. [36] takes makespan, total tardiness and total workload as optimizing objectives, a distributed ant colony system is proposed to explore the pareto front of FAJSS.…”
Section: Sets and Indicesmentioning
confidence: 99%
“… Wu et al (2019) considered the FAJSP based on the distributed workshop architecture and proposed a model considering tardiness, production, and transportation costs and designed a genetic algorithm to solve it. Lin et al (2022) studied FAJSP with a tight job based on a genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…They introduced two hybrid metaheuristic algorithms based on particle swarm optimization and variable neighborhood search to solve the problem with practical size dimensions. Lin et al (2020) studied the flexible assembly job shop scheduling with tight job constraints to minimize makespan as the objective function. A job constraint genetic algorithm was proposed in this study and the results showed that the suggested algorithm can obtain proper solutions in various dimensions of the problem.…”
Section: Introductionmentioning
confidence: 99%